Understanding business networks from a mixed network and system ontology position: A review of the research field. Issue 2 (12th June 2017) - Prenkert, Frans
Abstract : Purpose: The purpose of this paper is to highlight the ontological implications of combining network and system ontology to conceptualize industrial networks as the empirical manifestations of complex adaptive economic systems. Design/methodology/approach: This paper contributes with a systematic discussion on how network and system ontology can be combined to produce better understandings of business networks. It also provides a review of the state-of-the art research literature on the topic as a starting point for the discussion. Findings: Findings indicate that networks may be enclosed in each other constituting sub- and supra-networks comprising increasing complexity. In these cases, sub-networks that are black-boxed can be seen as entities in themselves producing inputs and outputs to the supra-network. Networks, once they become black-boxed, can assume the functions of generative mechanisms within a wider supra-network. Research limitations/implications: This research is conceptual in nature and needs to be complemented with empirical research. In addition, the literature review used one database complemented with papers from the IMP journal. A wider search could reveal additional research that can be of relevance for the development of the field. Originality/value: This paper addresses the ontological and methodological issues arising from a mixed system and network ontology. These issues are commonly ignored or dealt with indirectly in extant literature. For any accumulation of knowledge in the field to be possible, the explication of a mixed ontology is important as it have conceptual and methodological consequences. Adopting such a mixed ontological position provides an ontology in line with empirical research of business practice.